ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERKEMBANGAN SAHAM SYARIAH (STUDI EMPIRIS PADA BURSA EFEK INDONESIA) - Subur Karyatun (Universitas Nasional, 2018)
After sharia banks appears in Indonesia, the economic development is changing. The change occurs in the banking system namely Long Term Relations Jakarta Islamic Index (JII) in Indonesia Stock Exchange. The condition is interesting to examine, so some research on this has been done, here the purpose of this research is to analyze how the relationship influencebetween inflation, exchange rate of rupiah, interest rate and sharia stock.The independent variables used in this research are inflation data, rupiah exchange rate, interest rate and syariah stock as dependent variable. As representation of sharia stock price is company registered in JII and as sample there are 3 companies that is Ultrajaya, Telkom and Indosat. Tests conducted between the three independent variables of sharia shares. The research data is sourced from companies that issue Sharia shares in 2014-2016. The result shows that the three independent variables have an effect on to sharia stock.